Design, analysis and fabrication of mini car automated road and floor dust cleaning machine / Hedzry Shafry Redzuan Shafry and Suhadiyana Hanapi - Shafry, Hedzry Shafry Redzuan; Hanapi, Suhadiyana (School of Mechanical Engineering, 2022)
Mini Car Automated Road and Floor Dust Cleaning Machine is a prototype that will help people to do their cleaning process easier. The function of this machine is collecting debris such as dried leaves, dust, and rubbish while moving automatically. The machine will move in the straight line while the brush rolls the debris such as dust and dried leaves into the container inside the machine. Cleaning manually such as sweeping and mopping could take a lot of energy and work. With this prototype, the user will only need to adjust the position of the prototype and let the machine do the cleaning. This will ease the user and prevent any unnecessary injuries in the long term such as back pain and more. Besides that, cleaning manually could take a lot of time especially while cleaning big areas. With this machine, we can save time and do the cleaning activities systematically. The users will only need to take out the container that has collected the debris and dispose of it easily. Hence, this prototype will increase the work efficiency for the cleaning activities. With the help of this prototype, it will lighten the burden thus making the cleaning work easier and efficient